Fullerene attachment to sharp-angle nanocones mediated by covalent oxygen bridging - Suarez-Martinez, Irene; Mittal, Jagiwan; Allouche, Hatem; Pacheco, Marquidia; Monthioux, Marc; Razafinimanana, Manitra; Ewels, Chris (Pergamon, 2013)
Using a combination of transmission electron microscopy and density functional modeling we examine covalent bridging between carbon nanoforms, focusing on fullerene attachment to carbon nanocones (nanohorns). We show that oxygen mediates covalent cross-linking between carbon nanoforms, analogously to oxygen-mediated fullerene dimerisation (C120O). We confirm this theoretically and experimentally for fullerenes bonded to nanocone tips. Oxygen bridging only occurs in systems with relatively localized double bond character, i.e., in the case of nanocones, bridging only occurs between fullerenes and high angle nanocone tips.